DDoS attack aware environment with secure clustering and routing based on RPL protocol operation. Issue 6 (5th September 2019) - Alabsi, Basim Ahmad; Anbar, Mohammed; Manickam, Selvakumar; Elejla, Omar E.
Abstract : Routeing protocol for low‐power and lossy networks (RPL) are widely used in dynamic wireless sensor network. Several types of researches worked on RPL and designed hybrid energy‐efficient cluster‐parent‐based RPL, queue utilisation (QU)‐RPL, improved RPL, attack detection RPL etc. to support from vulnerable threats, provide efficient routeing and balance dynamic nodes in the network. Previous research findings dealt with certain limitations and problems. In this study, a new coordinative‐balanced clustering algorithm is proposed which is enabled to balance destination‐oriented directed acyclic graph (DODAG) that is formed in each cluster. Pruning of nodes from DODAG effectively maintains cluster with minimised complexity. This study also resolves the problem of two common security attacks such as distributed denial of service attack (DDoS) and version number attack. Then, enriched‐ant colony optimisation is used for DDoS detection and a secure route is chosen to perform data transmission. At the instance of selecting best parent for forwarding data, the authors use residual energy and scoring factor. Scoring factor of each node denotes the legitimacy to be selected as the best parent. Finally, results obtained from Network Simulator 3 indicate better performances on the following metrics: packet delivery ratio, end‐to‐end delay, node death minimisation, packet loss rate and power consumption.